The diversity of small‐scale oil palm cultivation in Sarawak, Malaysia. Issue 4 (14th August 2015) - Soda, Ryoji; Kato, Yumi; Hon, Jason
Abstract : The purpose of this study was to describe the patterns of land use that have emerged on the island of Borneo in the wake of an oil palm boom in its indigenous population. An in‐depth examination of indigenous land‐use changes between 2004 and 2013 in a selected oil palm farming village in Sarawak, Malaysia was conducted using data derived from high‐resolution satellite images to examine the spatial distribution of oil palm cultivation. The results found that oil palms are irregularly and randomly distributed. The results of interviews with villagers further revealed a diversity of oil palm planting actors and demonstrated how this diversity relates to villagers' land‐use options and decision‐making. From the viewpoint of plantation management, the mosaic and patchy cultivation of small‐scale oil palm farming appears inefficient and irrational. However, villagers' land‐use behaviours conform to their traditional land tenure customs and allow them to secure diverse opportunistic land‐use options to survive in the event of a sharp drop in the price of oil palm. The villagers' rationale for oil palm expansion also derives from their complex relationships with the diversity of actors that have interest in their land, including plantations, urban Chinese, and small‐ and middle‐scale developers. It is important to create balanced relationships among these diverse stakeholders in order to maintain mosaic‐like village landscape and realise sustainable development of oil palm cultivation in rural Sarawak.